Character Building of “Sanaman Mantikei” Folklore from Central Kalimantan - Afdalia, Tiara; Perdana, Indra; Luardini, Maria Arina (Institut Agama ISlam Negeri Palangka Raya, 2022)
The folklore entitled Sanaman Mantikei is one of the legends originating from Central Kalimantan. Folklore as literacy material can be used in the teaching and learning process to strengthen student character building. This study aims to describe the values of character building in the folklore legend